Decoding Ability of Students with Visual Impairment under Systematic and Explicit Phonics Instruction - Syuhadi, Mohammad Ryan; Susanto, Susanto; Setiawan, Slamet (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
This study discusses the decoding ability of students with visual impairment in a special need school under the implementation of systematic and explicit phonics instruction. The purpose of this study is to observe to what extent does the instruction help students with visual impairment in novice and mature alphabetic stage learn English word decoding. This qualitative study uses non-participant observation using unstructured fieldnotes and loosely-structured interview to obtain verbal data from 1 teacher and 4 students in four meetings of classroom observation. All of the students are visually impaired whom divided into two big groups. 2 of the students belong to mature alphabetic stage and the other 2 students belong to novice alphabetic stage. The classroom being observed is an English extracurricular classroom in a school specialized for students with visual impairment. Although they are divided into two groups, they study together in a same classroom at once. The results derived from the observation and interview are (1) Students in novice alphabetic stage, although they have not memorized all of the alphabet’s name, they still are able to gain knowledge of English word decoding, (2) Students in mature alphabetic stage, for they have memorized all of the alphabet’s name, have an easier understanding and are able to cope with the instruction better and faster, (3) this kind of instruction could gain students confidence in reading English word even though they do not memorize the alphabet’s name, (4) Once the students are able to relate between the words’ shape and how it sounds, they start to build automaticity in building their understanding of English words decoding. This study concluded that with appropriate materials and instruction, students with visual impairment in novice and alphabetic stage could acquire the knowledge of how to sound English words. Keywords: Decoding, Students with Visual Impairment, Systematic and Explicit Phonics Instruction